How I Manage Cancer-Associated Thrombosis - Moik, Florian; Ay, Cihan (Hämostaseologie, 2020)
In this concise review, we discuss some common clinical challenges in the management of patients with cancer-associated venous thromboembolism (VTE), a frequent complication in patients with cancer that increases morbidity and mortality. While direct oral anticoagulants (DOACs) have been established in clinical practice for anticoagulation in patients with VTE without cancer, their efficacy and safety in patients with cancer have not been assessed in randomized controlled trials until recently. The choice of the appropriate anticoagulant agent in the era of DOACs to treat patients with cancer-associated VTE is based on balancing the risk of recurrence against the risk of bleeding, and potential drug–drug interactions. However, the management of patients is challenged by special scenarios such as incidentally diagnosed pulmonary embolism and catheter-related thrombosis, and sometimes complicated by concomitant thrombocytopenia. We provide guidance for management of cancer-associated VTE in different clinical scenarios in a case-based manner and briefly review recent clinical studies and guidelines to explain our approach to management of the cases.
Keywords: cancer; thrombosis; venous thromboembolism; anticoagulation; DOAC